Growth of corneal epithelial cells over in situ therapeutic contact lens after simple limbal epithelial transplantation (SLET) - Bhalekar, Swapnil (BMJ Publishing Group, 2013)
An 11-year-old boy underwent simple limbal epithelial transplantation (SLET) from the healthy right eye to his left eye for total limbal stem cell deficiency. One month later, corneal surface epithelialised and whitish plaques overlying the transplants were seen inferiorly. Those plaques were adherent to the surface of the contact lens and underlying corneal surface had smooth elevations. Similar findings were noted in a 23-year man following cyanoacrylate glue application for corneal perforation. On histological and immunohistochemical analysis, cells lining the contact lenses were identified as corneal epithelial cells. These cases illustrate epithelial cell growth on the contact lens and epithelial hyperplasia on corresponding surface of the cornea. Exorbitant proliferation of the epithelial cells may be owing to young age; therefore, early contact lens removal after SLET in young age, can possibly avoid epithelial hyperplasia. This also reiterates the possibility of using contact lens as a scaffold to grow epithelial cells.